Coexistent sickle cell anemia and autoimmune hemolytic anemia in two adolescents - Vinícius Reis Soares; Bruna Paccola Blanco; Carla Luana Dinardo; Marlene Pereira Garanito (Einstein (São Paulo))
ABSTRACT The development of alloantibodies or autoantibodies is a complication observed in sickle cell disease. Autoimmunization occurs in 7.6-12% of chronically or intermittently transfused patients with sickle cell disease; however, the clinical implications of autoAbs are unclear. Few studies have focused on pediatric sickle cell disease and autoimmune hemolytic anemia. Herein, we present the coexistence of sickle cell disease and autoimmune hemolytic anemia in two adolescent patients, focusing on their pathophysiology, diagnosis, clinical management, and outcomes.